2011
DOI: 10.1016/j.yfrne.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal endocrine influences on sexual orientation and on sexually differentiated childhood behavior

Abstract: Both sexual orientation and sex-typical childhood behaviors, such as toy, playmate and activity preferences, show substantial sex differences, as well as substantial variability within each sex. In other species, behaviors that show sex differences are typically influenced by exposure to gonadal steroids, particularly testosterone and its metabolites, during early development (prenatally or neonatally). This article reviews the evidence regarding prenatal influences of gonadal steroids on human sexual orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(130 citation statements)
references
References 144 publications
(191 reference statements)
6
112
0
7
Order By: Relevance
“…Despite a male-typical level of T throughout fetal development, the genitalia of XX newborns with CAH are usually only partially masculinizedabout halfway between a typical male and female genital (Hall et al 2004), as is childhood sexually dimorphic behavior (Hines 2011). Although rates of homosexuality and transsexuality are elevated in CAH patients, the vast majority have female-typical sexual behavior (reviewed in Hines 2011). These data provide strong evidence that androgen-induced masculinization is blunted in the XX fetuses.…”
Section: Sex Hormone Differences Are Notmentioning
confidence: 88%
See 1 more Smart Citation
“…Despite a male-typical level of T throughout fetal development, the genitalia of XX newborns with CAH are usually only partially masculinizedabout halfway between a typical male and female genital (Hall et al 2004), as is childhood sexually dimorphic behavior (Hines 2011). Although rates of homosexuality and transsexuality are elevated in CAH patients, the vast majority have female-typical sexual behavior (reviewed in Hines 2011). These data provide strong evidence that androgen-induced masculinization is blunted in the XX fetuses.…”
Section: Sex Hormone Differences Are Notmentioning
confidence: 88%
“…This elevated level of T begins in the seventh week of gestation (Speiser and White 2003;Trakakis et al 2009) and "the developing fetus is exposed to the excessive adrenal androgens, equivalent to the male fetal level, secreted by the hyperplastic adrenal cortex" (New 2004), including the period of maximal average T excess in XY fetuses (Forest 1985). Despite a male-typical level of T throughout fetal development, the genitalia of XX newborns with CAH are usually only partially masculinizedabout halfway between a typical male and female genital (Hall et al 2004), as is childhood sexually dimorphic behavior (Hines 2011). Although rates of homosexuality and transsexuality are elevated in CAH patients, the vast majority have female-typical sexual behavior (reviewed in Hines 2011).…”
Section: Sex Hormone Differences Are Notmentioning
confidence: 99%
“…Although there are no definitive evidences for involvement of estrogen in human sexual brain differentiation, there are some from the "naturally occurring experiments". In the case of congenital adrenal hyperplasia (CAH), in which female fetus is exposed to elevated androgen levels, it is believed that there is some degree of masculinization of the brain consequent to fetal exposure to androgens [12]. Studies in the rat SDN-POA inspired the examination of human POA where a nucleus was found that was smaller in women than in men and smaller in gay men than in straight men [14,23].…”
Section: Brain Regions Preoptic Area Hypothalamus Pituitarymentioning
confidence: 99%
“…By the second trimester of gestation, male gonads have formed into functioning testes, thereby producing testosterone at higher levels than female ovaries [41,42]. This prenatal exposure to testosterone permanently organizes the brain in ways that promote greater physical activity throughout life [43,44]. As a consequence, males tend to be more active than females before birth as well as afterward.…”
Section: Discussionmentioning
confidence: 99%